CHARACTERISATION, IN SILICO AND IN VITRO DETERMINATION OF ANTIDIABETIC AND ANTI INFLAMMATORY POTENTIAL OF ETHANOLIC EXTRACT OF SARGASSUM WIGHTII. - Begum SM, Fazeela Mahaboob; S, Hemalatha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The current study was intended to investigate and characterize the phytoconstituents of Sargassum wightii ,evaluate its anti diabetic and anti inflammatory potential under in silico and in vitro conditions. Methods: The marine algae S.wightii was extracted with ethanol. The ethanolic extract was screened for various phytoconstituents, quantified for total flavonoid and polyphenol content. FTIR and Mass spectrometry was used for characterizing the ethanolic extract. Antidiabetic potential of the phytoconstituents was analysed by molecular docking and enzyme inhibition assays. The anti inflammatory potential was evaluated by albumin denaturation assay. Results: The phytochemical screening revealed the presence of flavonoids, polyphenols, alkaloids, tannins, carbohydrates, proteins, oils and fat present in the ethanol extract. The FTIR analysis showed the presence of α,b unsaturated ketone, alcohol and ether groups in the extract. MS analysis identified l - (+) - Ascorbic acid 2, 6 dihexadeconoate and Dotriacontyl isopropyl ether in the ethanolic extract. The molecular docking studies revealed that l - (+) - Ascorbic acid 2, 6 dihexadeconoate interacted with both α amylase and α glucosidase with a consensus score of 5.The results of in vitro analysis showed that the ethanolic extract exhibited strong inhibitory activity on α amylase (IC 50 8mg/ml) and α glucosidase (IC 50 6mg/ml) respectively. The ethanolic extract also inhibited the formation of advanced glycation end products (IC 50 10mg/ml).Further the ethanolic extract inhibited the denaturation of albumin (IC 50 2.5 mg/ml) there by revealing the anti inflammatory potential of S.wightii. Conclusion: Hence it can be concluded that S.wightii possess anti diabetic and anti inflammatory potential which may be due to the presence of l - (+) - Ascorbic acid 2, 6 dihexadeconoate and flavonoids, polyphenols, alkaloids, tannins, carbohydrates, proteins, oils and fat present in the extract. Key words: Sargassum wightii, α amylase, α glucosidase, advanced glycation end products, molecular docking.